(-2.9)8x-1=(-2.9)9x+4

Simple and best practice solution for (-2.9)8x-1=(-2.9)9x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-2.9)8x-1=(-2.9)9x+4 equation:


Simplifying
(-2.9) * 8x + -1 = (-2.9) * 9x + 4

Multiply -2.9 * 8
-23.2x + -1 = (-2.9) * 9x + 4

Reorder the terms:
-1 + -23.2x = (-2.9) * 9x + 4

Multiply -2.9 * 9
-1 + -23.2x = -26.1x + 4

Reorder the terms:
-1 + -23.2x = 4 + -26.1x

Solving
-1 + -23.2x = 4 + -26.1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '26.1x' to each side of the equation.
-1 + -23.2x + 26.1x = 4 + -26.1x + 26.1x

Combine like terms: -23.2x + 26.1x = 2.9x
-1 + 2.9x = 4 + -26.1x + 26.1x

Combine like terms: -26.1x + 26.1x = 0.0
-1 + 2.9x = 4 + 0.0
-1 + 2.9x = 4

Add '1' to each side of the equation.
-1 + 1 + 2.9x = 4 + 1

Combine like terms: -1 + 1 = 0
0 + 2.9x = 4 + 1
2.9x = 4 + 1

Combine like terms: 4 + 1 = 5
2.9x = 5

Divide each side by '2.9'.
x = 1.724137931

Simplifying
x = 1.724137931

See similar equations:

| 5z-8=33 | | x-24=-36 | | -7(6-4b)=98 | | h(x)=X^4-2x^3+14x^2+6x-51 | | (6x-3)+7=44 | | 9(21-1x)=17(2x+1) | | 3z+11+28z=50+29z-(-1) | | 4y-19y=60 | | -(4x+3)-(-3x-5)=3 | | 5x-4=5(2x-3) | | 10x-1(3x-2)=30 | | 2(x-3)=3y | | -5(4y-5)+20y= | | -4+3n=4(n+2) | | 4(5t+1)-8=t-(t-3) | | -5(2p+4)-22=3(3p+5) | | X^2+X-0.003=0 | | -2.5+8.9=2.5 | | -2.5+8.9=2.5 | | (-33)=(-17)-n | | (-33)=(-17)-n | | 21+21j+j+19j=125+2j | | -11m+3m=12-44 | | 2p^2+15p+13=0 | | 4t+4t=15+2-9 | | 3z=5z-24 | | 4(-6r-2)-2=-130 | | =2.44444444 | | 17x+1=-14 | | 1x-9=6 | | 8x+12y=1024 | | f(5)-f(3)= |

Equations solver categories